World Trade Center - Stone, Oliver; Berloff, Andrea; Shamberg, Michael; Paramount Pictures (Hollywood, Calif. : Paramount, 2006)
The true story of Port Authority policemen John McLoughlin and William J. Jimeno, who volunteered for rescue duty and became trapped in the rubble of the Towers on September 11, 2001. The men became two of the last survivors extracted from Ground Zero. It is a story of the true heroes and of that fateful time in United States history, when buildings would fall and heroes would rise, literally from the ashes to inspire the entire human race
Title from title screen
Based on the true life events of John & Donna MaLoughlin and William & Allison Jimeno
Executive producer, Donald J. Lee, Norm Golightly ; director of photography, Seamus McGarvey ; editors, David Brenner, Julie Monroe ; music, Craig Armstrong ; special effects supervisors, Martin Bresin, Chris Hampton ; visual effects supervisor, John Scheele
Casts: Nicolas Cage, Michael Pena, Maria Bello, Maggie Gyllenhaal
Keywords: McLoughlin, John -- Drama; Jimeno, William -- Drama; World Trade Center (New York, N.Y.) -- Drama; September 11 Terrorist Attacks, 2001 -- Drama; Rescues -- New York (State) -- New York -- Drama